2015
DOI: 10.1002/nur.21650
|View full text |Cite
|
Sign up to set email alerts
|

The Association of HIV Stigma and HIV/STD Knowledge With Sexual Risk Behaviors Among Adolescent and Adult Men Who Have Sex With Men in Ghana, West Africa

Abstract: Ghanaian men who have sex with men (MSM) have a high HIV seroprevalence, but despite a critical need to address this public health concern, research evidence has been extremely limited on influences on sexual risk behavior among MSM in Ghana. To investigate associations between HIV/STD knowledge, HIV stigma, and sexual behaviors in a sample of MSM in Ghana, we conducted a secondary data analysis of cross-sectional survey data from a non-probability sample of Ghanaian MSM (N = 137). Nearly all the men (93%) had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 82 publications
7
53
0
1
Order By: Relevance
“…This exercise is particularly important in the context of HIV since many of those most at risk are members of stigmatized or criminalized populations. In the case of RDS, egos are asked to refer alters who fit a particular profile, allowing detection and identification of specific high-risk populations (43), including people who use injection drugs (44)(45)(46), men who have sex with men (MSM) (47)(48)(49)(50)(51) and people who engage in sex work (52)(53)(54)(55). Similarly, qualitative descriptions of the social networks of at-risk populations can provide vital insights into the activities of at-risk groups, notably of the interactions between members, which can provide unique understanding about barriers and facilitators of intervention delivery (56,57).…”
Section: Using Social Network To Understand Hiv Treatment and Prevenmentioning
confidence: 99%
“…This exercise is particularly important in the context of HIV since many of those most at risk are members of stigmatized or criminalized populations. In the case of RDS, egos are asked to refer alters who fit a particular profile, allowing detection and identification of specific high-risk populations (43), including people who use injection drugs (44)(45)(46), men who have sex with men (MSM) (47)(48)(49)(50)(51) and people who engage in sex work (52)(53)(54)(55). Similarly, qualitative descriptions of the social networks of at-risk populations can provide vital insights into the activities of at-risk groups, notably of the interactions between members, which can provide unique understanding about barriers and facilitators of intervention delivery (56,57).…”
Section: Using Social Network To Understand Hiv Treatment and Prevenmentioning
confidence: 99%
“…This would also predispose their children to stigmatization [17]. In a conservative culture such as Ghana, people living with HIV are stigmatized in the community and sometimes in the hospitals [911]. Perhaps, the possibility of side effects after prolonged exposure of their children to the anti-retroviral medication if they contract HIV, may also be causing the fear in the mothers.…”
Section: Discussionmentioning
confidence: 99%
“…People living with HIV in Ghana are stigmatized [911]. In a Ghanaian study, it was found that, stigmatization of people living with HIV occurred not only in the community but also at the hospital [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 838 videotaped encounters from 10 completed trials conducted by the Knowledge and Evaluation Research Unit, Mayo Clinic (Rochester, Minnesota) 9 . Most of these trials included patients outside the referral practice of the Mayo Clinic and involved primary and specialty care, physicians and nurses, and emergency and ambulatory settings (Table 1).…”
Section: Methodsmentioning
confidence: 99%